x + 2 y = 17 si y - 3 z = 4
a) x + 3 y - 3 z = ( x + 2 y ) + ( y - 3 z ) = 17 + 4 = 21
______________________________________
b) 2 x + 5 y - 3 z = 38
= 2 × ( x + 2 y ) + ( y - 3 z ) =
= 2 × 17 + 4 =
= 34 + 4 =
= 38
_______________
c) ( 3 x + 6 y ) + ( 2 y - 6 z ) =
= 3 ( x + 2 y ) + 2 ( y - 2 z ) =
= 3 × 17 + 2 × 4 =
= 51 + 8 =
= 59
____________________________
d) ( 2 x + 4 y ) × ( x + 4 y - 6 z ) = 850
= 2 × ( x + 2 y ) × [ ( x + 2 y ) + 2 ( y - 3 z ) ] =
= ( 2 × 17 ) × ( 17 + 2 × 4 ) =
= 34 × 25 =
= 850